A Systematic Review and Meta-Analysis on Multiple Cytokine Gene Polymorphisms in the Pathogenesis of Periodontitis - Liu, Xin; Li, Hui (Frontiers in Immunology, 2022)
Aim Periodontitis is an inflammatory disease that destroys both soft and hard periodontal tissues. However, a complex periodontal cytokine network remains unclear. This systematic review explored multiple cytokine gene polymorphisms in the pathogenesis of periodontitis. Material and Methods A systematic search was performed using the databases from previous publications, which indicated the association between cytokine polymorphisms and periodontitis pathogenesis. Meta-analysis was conducted using fixed or randomized models to calculate the significance of multiple cytokine polymorphisms. A total of 147 articles were analyzed with polymorphisms in 12 interleukins [Th1 (IL-2, IFN-γ, and TNF-α), Th2 (IL-4 and IL-13), Th17 (IL-1α, IL-1β, IL-6, and IL-17), and Treg cytokines (IL-10 and TGF-β)]. Doi plot was used to probe the occurrence of publication bias. Results The polymorphisms of IL-2 and TNF-α of Th1 cytokine family may be associated with the pathogenesis or the prevention of periodontitis risk, while the polymorphism of IFN-γ is not related to periodontitis risk. The polymorphisms for IL-4 and IL-13 of Th2 cytokine family are not found to be associated with the pathogenesis of periodontitis. For the polymorphisms of the members of Th17 cytokine family, different IL-1α polymorphisms may have inverse actions in the pathogenesis of periodontitis. IL-1β is a noteworthy cytokine biomarker in periodontitis development and progression. IL-6 may have a protective function in the inflammatory responses of periodontitis, and IL-17 has a weak relationship the inflammatory responses. The polymorphisms for the members of Treg cell cytokines may have a protective function against periodontitis risk. LFK indexes show the major asymmetry due to publication bias. Conclusion IL-1β is a notable cytokine biomarker in periodontitis risk. Treg cytokines favor an anti-inflammatory and protective environment. Further data are needed to confirm the present conclusion due to publication bias.